Contribution of Process Standards, Content Standards and Infrastructure Standards Towards Graduate Competency Standards in SMA/SMK/SLB District of the Mentawai Islands - Bestri, Rafikah; Mures Walef, Sri; Rusdinal, Rusdinal; Hadiyanto, Hadiyanto; Daharnis, Daharnis (Universitas Negeri Padang, 2023)
This research aims to describe the contribution of process standards, content standards and infrastructure standards to graduate competency standards in high schools/vocational schools/special schools in the Mentawai Islands district . This research is explanatory research because it wants to know the object in depth. The data collected in this study was arranged based on an ordinal scale. The population to be studied in this research is SMA/SMK/SLB, Mentawai Islands Regency, totaling 18 schools. The sampling technique used in this research was the total sampling technique . This research uses two variables that will be involved, namely: 1. Independent variables are variables that influence the dependent variable. The technique used to collect data. First is a questionnaire, collecting data from respondents/primary data sources by asking a list of questions. written/questionnaire. The research results show that 1) there is a contribution of Process Standards to Graduate Competency Standards; 2) there is a contribution of Content Standards to Graduate Competency Standards. 3) there is a contribution of Facilities and Infrastructure Standards to Graduate Competency Standards. 4) there is a contribution of Process Standards and Content Standards to Graduate Competency Standards. 5) there is a contribution of Process Standards and Infrastructure Standards to Graduate Competency Standards. 6) there is a contribution of Content Standards and Infrastructure Standards to Graduate Competency Standards. 7) there is a contribution of Process Standards, Content Standards and Infrastructure Standards together to Graduate Competency Standards. In conclusion, there is a contribution of process standards, content standards and infrastructure standards to the competency standards of graduates in high schools/vocational schools/special schools in the Mentawai Islands districtKeywords: process standards, content standards, infrastructure standards, and graduate competency standards